Improving Physical Fitness Learning Outcomes for Coordination Through Traditional Block Running Games for Students - Rumiyani; Hartati; Pranoto S (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
The purpose of this study was to determine whether there was an increase in learning outcomes of Physical Fitness for Coordination in Class VIII students of SMP Negeri 3 Palembang after the implementation of the traditional game of running beams. Therefore, this study is expected to help solve the problems experienced and describe how much the learning outcomes of coordination and balance of movement increase through the traditional game of running beams. The method used in this study is action research. The population used was class VIII.3 students of SMP Negeri 3 Palembang. The sample used was 31 students using the population sampling technique or the entire population used as a sample. The instruments used in this study were observation sheets and data on the results of Learning Coordination and Balance of Movement in Physical Fitness which were carried out through learning outcome tests. The results of data processing and data analysis showed an increase in learning outcomes of Coordination and Balance of Movement in Physical Fitness for the first cycle increased by 58% and the second cycle increased by 90% from the data of 31 students. So the increase in data from the first and second cycles increased by 32%.